Relationship Of Pregnant Mother's Anxiety Levels During The Covid-19 Pandemic On ANC Visit At Puskesmas Sukatani Bekasi - Wiwit Astuti; Sri Dinengsih; Shinta Novelia (Jurnal MIDPRO, 2021)
The spread of the Covid-19 pandemic in Indonesia has made vulnerable groups more susceptible to contracting this virus. One of these vulnerable groups is pregnant women. More and more pregnant women in Indonesia are positive for Covid-19. Pregnant women who are infected with the Covid-19 virus are more likely to give birth to babies early in premature conditions. During the Covid-19 pandemic, many pregnant women were afraid to have their pregnancy checked. Anxiety when they want to do a pregnancy check is often felt by pregnant women during a pandemic corona virus. Analytical research using the "cross-sectional" method. The sample in this study amounted to 178 respondents. The sampling technique used was accidental sampling. The research instrument is a questionnaire. Data were analyzed using univariate and bivariate with chi square statistical test. Univariate results showed the majority of severe anxiety levels and the majority of ANC visits were irregular. The results showed that there was a significant relationship between the anxiety of pregnant women during the Covid 19 pandemic and ANC visits with a p value <0.05.